Psychological empowerment and job satisfaction in nurses: A systematic review and meta-analysis - Gu, Lihua; Wang, Liping; Pan, Biwei (Frontiers in Public Health, 2022)
Background: Psychological empowerment was reported to be associated with job satisfaction among nurses. However, recent published literatures observed inconsistent results on the association. Objective: We aimed to systematically investigate the association of psychological empowerment in nurses with job satisfaction. Methods: PubMed, Medline, Cochrane Library, PsycInfo, and Embase were used to search targeted studies from conception to January 20, 2022. The correlation coefficients of each study were extracted and converted into Fisher’s Z. Finally, pooled r was calculated by Fisher’s Z and standard error (se). Results: A total of 28 studies encompassing 27 articles with 7664 registered nurses were included. The pooled correlation coefficient between psychological empowerment and job satisfaction for was 0.55. Subgroup analyses were conducted according to ethnicity, and the correlation in the Asian participants (P < 0.01) was significantly stronger (P < 0.05) than that of the Caucasians (P < 0.01). Conclusions: Psychological empowerment is strongly correlated to job satisfaction for registered nurses, especially among those from Asian countries. The intervention by psychological empowerment could be one of the strategies promoting nurse retention. Nonetheless, additional future studies are essential for more investigations.